Does working at home compromise mental health? - Perelman, Julian (2021)
Introduction: The COVID-19 pandemic has transformed working at home (WAH) into the exclusive mode of working for many European workers. Although WAH will likely remain after COVID-19, its consequences on workers' health are unclear. This study examines the association of WAH and the change of four mental health (MH) domains. Methods: We used data from the last wave of the Survey on Health, Aging, and Retirement in Europe, collected in June and July 2020 on European people aged 50 and older. We restricted our analysis to people aged 50–65 who were working before COVID-19 (N = 7065). We modeled the risk of worsening of depression and anxiety feelings, sleeping trouble, and feelings of loneliness as a function of the working situation (usual setting, at home and usual setting, at home only), using logistic regressions. A first model adjusted for sociodemographic variables, a second one adding country fixed effects, and the last one adding the stringency of COVID-19-related restrictions. Results: WAH was significantly associated with a worsening of all MH symptoms. Nevertheless, when the stringency index was factored in, no significant association of WAH was found with any of the health outcomes except for anxiety feelings (+4.3% points). However, the increased anxiety feelings among people in WAH were not greater than the one observed among nonworkers. Discussion: Our findings show that WAH was not a major cause of mental health deterioration among European mature adults during the first month of the pandemic. Further evidence is needed on WAH under post-COVID-19 “normal” circumstances.